Eustress, Employee Job Burnout Syndrome and Productive Performance in the Madura Herbal Industry - Firdaus, Vera; Andriani, Dewi; Febriansah, Rizky Eka (Jurnal Manajemen Indonesia, 2023)
Herbal products require employees to maintain cleanliness and product quality, while on the other hand, the demand for herbal products has implications for increasing workloads and becoming stressors for employees. Efforts to optimize employee productivity and performance can be carried out by the company by revitalizing employee performance so that they remain productive. The novelty in this study is a combination of work productivity and performance dimensions that produce five indicators, namely work quality, work quantity, task performance, contextual; performance, and adaptive to timeliness. This study aims to identify the factors that affect the productive performance of employees. This study uses a quantitative approach with a questionnaire as primary data, which is analyzed using multiple linear regression analysis with testing using SPSS version 16 for Windows. The research population is the herbal family business employee in Madura. With the cluster sampling technique, 100 employees were obtained from 4 research locations in Bangkalan and Pamekasan. The results showed that eustress can increase the productive performance of employees. Meanwhile, high job burnout reduces the productive performance of employees. Keywords—Eustress; Job Burnout; Productive Performance